Potential of lactic acid bacteria in aflatoxin risk mitigation - Ahlberg, Sara H.; Joutsjoki, V.; Korhonen, H.J. (Elsevier, 2015)
Aflatoxins (AF) are ubiquitous mycotoxins contaminating food and feed. Consumption of contaminated food and feed can cause a severe health risk to humans and animals. A novel biological method could reduce the health risks of aflatoxins through inhibiting mold growth and binding aflatoxins. Lactic acid bacteria (LAB) are commonly used in fermented food production. LAB are known to inhibit mold growth and, to some extent, to bind aflatoxins in different matrices. Reduced mold growth and aflatoxin production may be caused by competition for nutrients between bacterial cells and fungi. Most likely, binding of aflatoxins depends on environmental conditions and is strain-specific. Killed bacteria cells possess consistently better binding abilities for aflatoxin B1 (AFB1) than viable cells. Lactobacilli especially are relatively well studied and provide noticeable possibilities in binding of aflatoxin B1 and M1 in food. It seems that binding is reversible and that bound aflatoxins are released later on (Haskard et al., 2001; Peltonen et al., 2001). This literature review suggests that novel biological methods, such as lactic acid bacteria, show potential in mitigating toxic effects of aflatoxins in food and feed.